Reactivity to uncertain threat as a familial vulnerability factor for alcohol use disorder. Issue 16 (14th September 2016) - Gorka, S. M.; Hee, D.; Lieberman, L.; Mittal, V. A.; Phan, K. L.; Shankman, S. A.
Abstract : Background: When sober, problematic drinkers display exaggerated reactivity to threats that are uncertain (U-threat). Since this aversive affective state can be alleviated via acute alcohol intoxication, it has been posited that individuals who exhibit heightened reactivity to U-threat at baseline are motivated to use alcohol as a means of avoidance-based coping, setting the stage for excessive drinking. To date, however, no study has attempted to characterize the dispositional nature of exaggerated reactivity to U-threat and test whether it is a vulnerability factor or exclusively a disease marker of problematic alcohol use. Method: The current investigation utilized a family study design to address these gaps by examining whether (1) reactivity to U-threat is associated with risk for problematic alcohol use, defined by family history of alcohol use disorder (AUD) and (2) reactivity to U-threat is correlated amongst adult biological siblings. A total of 157 families, and 458 individuals, participated in the study and two biological siblings completed a threat-of-shock task designed to probe reactivity to U-threat and predictable threat (P-threat). Startle potentiation was collected as an index of aversive responding. Results: Within biological siblings, startle potentiation to U-threat [intraclass correlation (ICC) = 0.35] and P-threat (ICC = 0.63) was significantly correlated. In addition, independent of an individuals' own AUD status, startle potentiation to U-threat, but not P-threat, was positively associated with risk for AUD (i.e. AUD family history). Conclusion: This suggests that heightened reactivity to U-threat may be a familial vulnerability factor for problematic drinking and a novel prevention target for AUD.